Three-Year Follow Up of Customized Glass Fiber Esthetic Posts - Costa, Rogério Goulart da; Morais, Eduardo Christiano Caregnatto de; Leão, Moira Pedroso; Bindo, Márcio José Fraxino; Campos, Edson Alves; Correr, Gisele Maria (European Journal of Dentistry, 2011)
Customized glass fiber posts that is well adjusted into the root canal and have mechanical properties similar to those of dentin may be a suitable treatment for severely compromised endodontically treated teeth. This article reports a 3-year follow up of severely damaged endodontically treated teeth restored with unidirectional fiber glass customized post and core system instead of a conventional fiber post. The fabrication of this glass fiber customized post is a simple technique, providing an increased volume of fibers into the root canal, and an adequate polymerization of the post-core system. Over a three-year period, the treatments demonstrated good clinical and radiographic characteristics, with no fracture or loss of the post and/or crown. This technique can be considered effective, less invasive, and suitable for restore endodontically treated teeth. (Eur J Dent 2011;5:107-112)
Keywords: Fiber-reinforced composite; Post and core system; Intraradicular retention; Oral rehabilitation